The Impacts of Outsourcing on Business Process Automation Implementation : A Comprehensive Analysis - Noudogbessi, Clara (My University, 2023)
This master thesis presents a comprehensive analysis of the multifaceted impacts of outsourcing on different phases of Business Process Automation (BPA) implementation. Through interviews with specialists involved in BPA outsourcing, valuable insights were obtained regarding the experiences, perspectives, and challenges faced by organizations during various stages of BPA implementation. The study identified key findings in each phase, highlighting the importance of involving external vendors from the start, establishing effective communication channels, and addressing regulatory hurdles. Additionally, concerns related to knowledge loss and dependency on external vendors were explored, emphasizing the significance of documentation and knowledge transfer practices. The findings align with existing literature on outsourcing and BPA, while also providing unique contributions by emphasizing the establishment of a specific vocabulary, linking outsourcing to regulatory challenges, and offering practical insights for managing outsourcing risks. The implications for theory suggest the need for careful management and coordination throughout the outsourcing process, as well as the significance of early vendor engagement. Practically, the study offers recommendations for organizations, including the involvement of external vendors from the beginning, proactive planning for potential challenges, and the adoption of specific strategies to enhance vendor relationships and project monitoring. The study acknowledges limitations and suggests future research directions, such as exploring different industries and regions, incorporating quantitative data, examining decision-making processes, and investigating the long-term sustainability of outsourcing arrangements. Overall, this master thesis provides a nuanced understanding of the impacts of outsourcing on BPA implementation, offering practical recommendations for organizations seeking successful outcomes in their automation journey.
Keywords: Outsourcing, Business process automation